Improving Students Writing Skills by Using Picture Series on Descrptive Text - Cindya S Simanjuntak; Meliana Siahaan; Agustinus Simamora (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
The purpose of the research is to provide students with a method to treat and facilitate the process of learning to write descriptive passages, thereby improving students' English writing skills using the Picture Series. Participants are 8th grade students of Pematangsiantar College 1 academic year 2022/2023 with 32 students. The study used CAR with two cycles to observe student activities and reactions in the classroom. The results of the study can be seen in the improvement of scores from pre-test to post-test 2 with a minimum score of 75 and a maximum score of 85 in post-test 2.